Effect of Polyethylene Glycol Immobilized into a Polymethacrylate Matrix on the Sorption of Rhodamine - Gavrilenko M. A. Mikhail Alekseevich; Gazieva E. A.; Gavrilenko N. A. Natalia Airatovna; Kirsanova I. V. (2015, 2015)
Title screen